The Taxonomical And Ecological Studies Of Phytoplankton And Benthic Microalgae In Teluk Bahang, Penang - Javeed, Aysha Mariam Mohamed (2020)
Variations in the composition of waters and sediment play an important role in regulating the temporal distribution and abundance of phytoplankton and benthic microalgae. This study examined the taxonomic composition, and study the temporal variability of benthic microalgae and phytoplankton in relation to water quality and environmental parameters. The sample collections were carried out monthly during low tide along the intertidal zone at Teluk Bahang, Penang for 18 months. A total of 11 in situ measurements were studied such as physical variables (salinity, temperature, pH, and dissolved oxygen), chlorophyll a biomass (water and sediment), pore and surface water nutrients (NO2 -, NO3 -, NH3, PO4 3-, and SiO2). In this study, a total of 59 species were found in benthic (station A and B) and subtidal area (station C) of Teluk Bahang. Benthic microalgae species at two benthic stations (Station A and B) were dominated by Baccillariophyta (100 %) and phytoplankton species (Station C) were dominated by Baccillariophyta (87.76%) and Dinophyta (12.24 %). Station A and B were dominated by same species of diatom which is Navicula menisculus and in Station C, Bellerochea horologicalis dominated the subtidal area. The species Navicula menisculus had the highest percentage of the overall diatom species composition in both station A during dry months (13.9%) and in station B (30.6%) during wet months. While in station C, the dominant species Bellerochea horologicalis had the highest percentage of the overall phytoplankton species composition (61.1%) during dry months.